Electronic branching ratio of the lepton - AMMAR, R. (Institutional Knowledge at Singapore Management University, 1992)
Using data accumulated by the CLEO I detector operating at the Cornell Electron Storage Ring, we have measured the ratio R=Γ(τ→eν¯eντ)Γ1 where Γ1 is the τ decay rate to final states with one charged particle. We find R=0.2231±0.0044±0.0073 where the first error is statistical and the second is systematic. Together with the measured topological one-charged-particle branching fraction, this yields the branching fraction of the τ lepton to electrons, Be=0.192±0.004±0.006.